UGC Guidelines on Sustainable and Vibrant University- Industry Linkage System for Indian Universities, 2024 - Dr. H M Naveen (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The NEP 2020 recommends for vibrant University-Industry linkage with an emphasis on exposing students to real-life situations and making them globally competent. Keeping this in view, the UGC has approved the guidelines entitled “A Sustainable and Vibrant University-Industry Linkage System for Indian Universities”. These guidelines will promote research and development through collaborations between universities and industries. Establishing the linkages between university and industry will help to create training and apprenticeship opportunities in the industries, R&D labs and research organizations. The Higher Educational Institutions (HEIs) have been advised by the UGC to initiate necessary measures to research and development by creating R&D clusters at the State or Regional levels through University-Industry (UI) linkages. These guidelines shall promote research and development through collaborations between Universities and Industries. It will also help students to develop skill sets among learners and make them fit for industrial skills through internships, including fields/industry/ on the job skills/vocational training/ life skills to achieve the learning objectives and attain desired outcomes effectively. Establishing the linkages between the university and the academic world will help to create training and apprenticeship opportunities for students in the industries, R&D labs, as well as in research organizations. Keeping all these aspects in view, the UGC approved guidelines for University-Industry linkages enlightens the practicians with regard to Objectives of the scheme; Mechanisms to boost R&D through University-Industry Linkages; University-Industry (UI) linkages for enhancement of student internship and apprenticeship in academic and industrial systems; and sustainability of the proposed UI linkage system. The present article will enlighten all the academicians to establish sustainable and vibrant linkage between Indian universities and industries.